Mechanistic insights into lenacapavir-induced off-pathway HIV-1 capsid assembly - Manish Gupta; Curt Waltmann; Nadine Renner; Yihang Wang; Leo C. James; David A. Jacques; Till Böcking; Gregory A. Voth (Proceedings of the National Academy of Sciences, 2026)
The HIV-1 capsid is a fullerene cone composed of hexameric and pentameric capsid proteins (CA) that packages the viral genome and mediates nuclear entry. Lenacapavir (LEN), a potent molecular long-acting inhibitor developed by Gilead, disrupts capsid morphogenesis by binding a phenylalanine–glycine (FG) pocket at the interface between adjacent CA subunits. Interestingly, cellular polyanion inositol hexakisphosphate (IP6) promotes conical capsid assembly by coordinating the central pore, which is allosterically coupled to the FG pocket. Because LEN and IP6 engage overlapping structural elements, they can compete to influence the capsid assembly pathway and outcomes. Using coarse-grained molecular simulations, we show that LEN accelerates hexamer formation while suppressing pentamer incorporation, yielding malformed, multilayered, and incomplete capsids. Simulations incorporating a ribonucleoprotein model further reveal that LEN-treated capsids often fail to encapsulate RNA, indicating impaired maturation. Our calculations confirm that LEN impairs the formation of high-curvature CA lattice regions necessary for closure, supporting a model of off-pathway assembly as a mechanism of viral inhibition. These findings define the core mechanism by which a small-molecule inhibitor disrupts the much larger-scale HIV-1 morphogenesis and underscore general principles for targeting self-assembling multi-protein complexes.